Immigrant shepherds in Mediterranean Europe - Nori M. (Innovation for sustainability in sheep and goats, 2019)
This paper examines recent evolutions of Mediterranean European Union (EUMed) countries agropastoral systems, and the problems faced following territorial polarization and sectoral restructuring the region has undergone in recent decades. In most southern EU regions the growing presence of immigrants have come to counterbalance the decline and ageing of the local rural population and agricultural workforce. The work specifically examines the presence, contribution and role of immigrant shepherds, who reached southern Europe from other pastoral areas in the Mediterranean, coming to provide skilled labor at a relatively low cost. Despite this phenomenon seems to reproduce mobility patterns that have characterized Mediterranean pastoralism in the last century, problems exist in integrating and upgrading such workforce with a view to tackle the generational renewal problems that affect the sector, and the EU countryside more in general. The paper suggests that a proactive attitude is needed to facilitate the scaling up of these workers to more entrepreneurial levels and more in general to enhance their long-term integration into the sector – with view to ensure their contribution to the future of pastoralism in the region.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)